Eligibility of MEMS Accelerometer As Velocitymeter - Rinda S. Ariyani; Didik R. Santoso; Ahmad Nadhir (Natural B, Journal of Health and Environmental Sciences, 2015)
Vibration can be measured by measuring each of several parameter, for example displacement, velocity and acceleration.There are many sensor that can be used in this measurement. Velocitymeter and accelerometer are the examples of vibration sensors. Accelerometer, generally use to measure acceleration, can be modified to measure velocity of vibration as the velocitymeter done. Accelerometer MEMS MMA7361L with the signal conditioning circuits, that is band pass filter and integrator, had been designed and assembled to measure the velocity of vibration. Velocity signal is produced in this circuit because of the integration process from integrator circuit. In design application, this circuits have a good performance in low frequency measurement like the velocitymeter done. But in practical, there are some deficiencies. This circuits can measure 0,86 Hz – 2,99 Hz frequency of low amplitude signal. The signal that is measured is about 1 volt below. Signal also have some distortion in negative swing. Hence, other new component for this real design is very needed to upgrade the performance of circuit in producing a good and non distortion signal for recording and displaying system easily. The output signal of circuit is velocity signal but it is still cannot be said to be the true measuring data. By adding calibration and the right formula, the magnitude of velocity can be gainned, so that this circuit can be said to be feasible as velocitymeter.